TEACHER EDUCATION IN POLAND: STRUCTURE AND CONTENT - Krystopchuk, T. (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the structure and content of teacher education in the Republic of Poland. Kinds of teacher training programmes and specialties for different types of educational institutions, types of educational institutions, which trains teachers with higher education on Licentiate and Master programmes for preschool and primary school in Poland, the main objectives of teacher training in high schools are defined. Plans and curricula reflecting the content of future teacher training are analyzed. The key documents that govern the system of professional growth and problems of teachers’ employment in Poland are listed The categories of teachers working in the school system, the qualification requirements for applicants for the post of a teacher, core competencies, which should have a modern teacher, forms of teachers’ professional development in Poland are specified. It was found that twoprofile training of future teachers in Poland provides a combination of training teachers for preschool institutions and for primary school. Teacher training is carried in three ways: fulltime, part time, evening.